The Characteristics of the Kapok (Ceiba pentadra, Gaertn.) Seed Oil - Berry, Shiv K. (1979)
The Malaysian Kapok (Ceiba pentadra) seeds were found to contain about 28 per cent oil. The oil from both raw and roasted seeds produced a positive Halphe'Jl test for cyclopropenoid fatty acids. Acid value, fatty acid composition by gas-liquid chromatography, iodine value, refractive index, saponification number, and unsaponifiables of the oil were also determined. The values (area percent) for fatty acids as methyl esters were: Cf4:0 (0.25%), C16:0 (24.31%), C16:1 (0.4%), C18:0 (2.65%), C18:1 (21.88%), C18:2 (38.92%), C20:0 plus C18 :3 (1%), malvalic acid (7.18%), C22:0 (0.44%), and sterculic acid (2.96%). Nlalvalic and sterculic acids were determined as AgNOrCH30H derivatives of their methyl esters. Since the cyclopropenoid fatty acids bring about a number of abnormal physiological effects in experimental animals, it would be extremely unwise to consume these seeds.